Violent Affections Queer sexuality, techniques of power, and law in Russia - Kondakov, Alexander Sasha (FRINGE, 2022)
Violent Affections uncovers techniques of power that work to translate emotions into violence against queer people. Based on analysis of over 300 criminal cases of anti-queer violence in Russia before and after the introduction of 'gay propaganda' law, the book shows how violent acts are framed in emotional language by perpetrators during their criminal trials. It then utilises an original methodology of studying 'legal memes' and argues that these individual affective states are directly connected to the political violence aimed at queer lives more generally. The main aim of Violent Affections is to explore the social mechanisms and techniques that impact anti-queer violence evidenced in the reviewed cases. Alexander Sasha Kondakov expands upon two sets of interdisciplinary literature - queer theory and affect theory - in order to conceptualise what is referred to as neo-disciplinary power. Taking the empirical observations from Russia as a starting point, he develops an original explanation of how contemporary power relations are changing from those of late modernity as envisioned by Foucault's Panopticon to neo-disciplinary power relations of a much more fragmented, fluid and unstructured kind - the Memeticon. The book traces how exactly affections circulate from body to body as a kind of virus and eventually invade the body that responds with violence. In this analytic effort, it draws on the arguments from memetics - the theory of how pieces of information pass on from one body to another as they thrive to survive by continuing to resonate. This work makes the argument truly interdisciplinary.